Medida aleatoria de Poisson - Beltrán, Johel (2013)
In this monograph we continue with the inspection initiated in [1] on the fundamental tools introduced in the approach proposed in [2,3] for the study of metastability. We give the definition of the Poisson random measures and prove the main properties that we will subsequently use to construct Markov processes with finite state space. Such construction will allow us to provide a probabilistic proof of the fact that the law of a Markov process solves the martingal problem.